Can someone help with with a question please? >Using Quadratic Formula and/or Substitution solve: ((t^2) -7) - 3((t^2) -7) + 2 = 0 (t^2) = T to the second power

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Can someone help with with a question please? >Using Quadratic Formula and/or Substitution solve: ((t^2) -7) - 3((t^2) -7) + 2 = 0 (t^2) = T to the second power

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

expand the problem and see what it gets you
heres what i got so far. : Using the quadratic formula: (Substitution) U = ((t^2) - 7) ==> u^2 - 3u + 2 ==> Quadratic Formula ==> 3 +- sqrt{9+8 ==> Answer that i got was : 3 (plus or minus) sqrt{ 17} divided by 2
Is this correct?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

not according to the question you posted; is the original typoed?
hmm shoot yes it is, im so sorry. its : ((t^2) - 7)^2 - 3((t^2) -7) + 2 = 0
ok..... your quadratic formula has issues to it; you seem to have forgotten to /2a
Um at the end of my answer i stated "Divided by 2"
i see it; its was lost in the formating lol
sqrt(b^2 -4(a)(c))...youve got a +4(a)(c)
3 sqrt[9-8] --- +- -------- 2 2
Wow, i cant believe i made that mistake.
your answers should end up as : t^2 -7 = 1 and t^2 -7 = 2
you slow typing ? :)
May i ask, after the 3+- sqrt { 9-8} = 3+- sqrt {1} ----------- 2 so ==> it'd be 3+ 1 \2 || 3-1 \2?
im at work sorry lol
lucky you; i aint got a job ...
yes; as long as i see it correctly; you did that right
:D thanks for your help. And oh on that note, ill be unemployed by the end of this month. :( Work place is closing shop. ----- Quick confirmation: final answer = final answers = 2 and 1 correct?
the final answer is to solve for t....not u :) final answers should be: +- 2sqrt(2) and +-3
ah... if i may, how did you arrive at that?
u = 1 = t^2-7 u=2=t^2-7 8=t^2 9=t^2 +-2sqrt(2) +-3
:D thanks man. i get it (mostly :P) this sites awesome :) i think i might post here for help some other time
:) good luck

Not the answer you are looking for?

Search for more explanations.

Ask your own question